The Utilization of MOOCs Using Kahoot and Student Engagement in Digital Learning During Covid-19 Pandemics - Rakhmat Wahyudin Sagala; Tri Indah Rezeki (Association of Language Teachers in Southeast Asia (ALTSA), 2022)
New technology advancements have frequently been credited as holding the potential to cause significant contributions to education. This study contributes to high-quality learning by putting students in real-world e-learning situations while still allowing them to use scientific techniques to complete their project assignments. The subjects of this study were 80 first-year undergraduate students enrolled in the Bahasa Inggris (English) course. The snowball method questionnaire was obtained, and questionnaires were distributed to the students’ WhatsApp groups by performing snowball operational. The Lectures combined virtual face-to-face video conferencing applications on e-learning. Kahoot is an add-on application used. In general, online learning has a positive effect on students’ learning success. However, there are still learning obstacles in academic performance in online learning. On the other hand, learning obstacles occur because of students' limitations in developing themselves or their mental readiness to learn. As a result, digital learning may blend real issues with theoretical concepts in the classroom without neglecting the learning objectives that have been set for student engagement.